2015
DOI: 10.1007/s40520-015-0366-8
|View full text |Cite
|
Sign up to set email alerts
|

Organ and tissue-dependent effect of resveratrol and exercise on antioxidant defenses of old mice

Abstract: Our data suggest that physical activity and resveratrol may be of great importance for the prevention of age-related diseases, but that their organ-dependent effect must be taken into consideration to design a better intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Interestingly, in previous studies, more of the 80% of age-related changes in gene expression found in skeletal muscle were partially or completely suppressed by early onset of CR in mice (Lee et al 1999). These different results probably indicate an age-dependent effect of CR, as we have found in murine models (Rodriguez-Bies et al 2015;Tung et al 2015b).…”
Section: Mitochondrial Activity and Ros Production Are Modulated By Crmentioning
confidence: 52%
See 3 more Smart Citations
“…Interestingly, in previous studies, more of the 80% of age-related changes in gene expression found in skeletal muscle were partially or completely suppressed by early onset of CR in mice (Lee et al 1999). These different results probably indicate an age-dependent effect of CR, as we have found in murine models (Rodriguez-Bies et al 2015;Tung et al 2015b).…”
Section: Mitochondrial Activity and Ros Production Are Modulated By Crmentioning
confidence: 52%
“…These discrepancies could be due to differences in the amount of time under CR or the degree of CR which can play an important role in nutrient balance. Further, as has been indicated in antioxidant responses (Rodriguez-Bies et al 2015;Tung et al 2015b), the age of the organism can be an important factor in the importance of each component that responds to CR.…”
Section: Igf-imentioning
confidence: 86%
See 2 more Smart Citations
“…Exercise can also act as a mild stressor that promotes adaptations leading to antioxidant defense system fortification, improved mitochondrial function, and induced redox remodeling (Cobley et al 2015; Navarro et al 2004; Ristow and Schmeisser 2014; Tung et al 2015). …”
Section: Antioxidant Intake and Moderate Exercise As Interventionsmentioning
confidence: 99%